CHEMICAL AND SENSORY EVALUATION OF FLAT BREAD SUPPLEMENTED WITH PEARL MILLET AND SOY PROTEIN ISOLATES - PARAMJOT KAUR; MONIKA SOOD; JULIE D. BANDRAL (The Bioscan, 2024)
n the present study flat bread was prepared by incorporation of 10, 20, 30 and 40 per cent of pearl millet flour with refined wheat flour and 10 per cent of soy protein isolates. The developed flat bread was stored for 18 days under refrigerated conditions to ascertain the changes in chemical and sensory characteristics. The magnesium content was observed maximum (116.56mg/100g) in T1 (00: 100: 00:: pearl millet flour: refined wheat flour: soy protein isolates/whey protein isolates) whereas, T6 (40:50:10:: pearl millet flour: refined wheat flour: soy protein isolates) recorded maximum calcium (43.93 mg/100g) and phosphorus content of 328.91mg/100g. Highest phytic acid content of 274.03 mg/100g and polyphenols content of 339.47 mg/100g were recorded in T6 (40:50:10:: pearl millet flour: refined wheat flour: soy protein isolates) which differed significantly with rest of the treatments. There was a significant increase in free fatty acid content during 18 days of storage from 0.98 to 1.56 % as oleic acid. Thus on the basis of sensory evaluation (colour, texture and taste), the incorporation of pearl millet flour upto 20 % along with 10 % soy protein isolates were considered acceptable for development of flat bread.